PENGEMBANGAN APLIKASI DASHBOARD POINT OF SALE SUPERMARKET (Information Technology and Telematics, 2015)
Abstract— In  the  current  era  of  globalization,  the development  of  technology  is  growing  rapidly.  And  in  the delivery of an information technology such as information about the data in a supermarket. Utilization of information relating to the supermaket here is how the supermarket manager can obtain the  information  needed.  That  information  will  facilitate managers  in  obtaining  the  data  without  having  to  look  at  the database into existing systems in supermarkets.Dashboard  Application  Development  Point  Of  Sale Supermarket is a combination of point of sales applications by using  a  web  service  that  will  be  used  as  a  bridge  for  display data  and  form  a  dashboard  view  that  displays  the  data information into the form of a graph. Supermarket manager can obtain  data  effectively  and  efficiently  by  using  a  dashboard point of sale application that uses web services technology.Keywords : Dashboard, Visualization, Web service